ISLAM DI TENGAH PUSARAN ARUS GLOBALISASI - Tsalis Muttaqin (UIN Raden Mas Said Surakarta, 2014)
Globalization, is not only offering something new about theconcept, but also the revolution. Globalization with its expectations,has the real effect in our lives as individuals, communities andcountries, as well as the world community. Global phenomenoncontinues with higher acceleration along with the development ofscience and technology. Ironically, this phenomenon occurs due to thechaos of inter-state relations, terrorism, and new model of colonialism.Regarding with the condition, religious teachings should not blame onthe conditions. Religion as a patron of morality should be able to faceon the globalization happening in the world. Religion should notbecome the victim of globalization itself. Religion should also be ableto direct the globalization that tends to be destructive intoenlightening.